Nociceptive phenotype of dorsal root ganglia neurons innervating the subchondral bone in rat knee joints. (2nd July 2013) - Aso, K.; Ikeuchi, M.; Izumi, M.; Sugimura, N.; Kato, T.; Ushida, T.; Tani, T.
Abstract Background The subchondral bone of the distal femur is a source of pain caused by osteoarthritis (OA) or spontaneous osteonecrosis of the knee. However, nociceptive phenotype of dorsal root ganglia (DRG) neurons innervating the subchondral bone in rat knee joints has not been clarified. Methods Retrograde labelling was used to identify afferents innervating the subchondral bone of the distal femur and the knee joint in rats. The nociceptive phenotype markers [calcitonin gene‐related peptide (CGRP), tyrosine receptor kinase A (TrkA), neurofilament 200 (NF200) and isolectin B4 (IB4)], segmental distribution and the soma size of backlabelled DRG neurons were examined. Furthermore, we evaluated the differences in nociceptive phenotype between the subchondral bone and the knee joint afferents. Results The majority (60%) of the subchondral bone afferents were localized in L3 DRGs and fewer in L4 and L5, while the knee joint afferents were localized mainly in L3 and L4. The percentage of CGRP immunoreactive (IR), TrkA‐IR, NF200‐IR and IB4‐binding neurons in the subchondral bone afferents were 50%, 65%, 35% and 0%, respectively. The percentage of CGRP‐IR and TrkA‐IR neurons in the subchondral bone afferents was significantly higher than that in the knee joint afferents, respectively (p < 0.05). Conclusion The majority of sensory DRG neurons innervating the subchondral bone of the distal femur were CGRP‐IR and TrkA‐IR. It is expected that therapeutic approaches targeting CGRP and TrkA could be effective in attenuating pain from the subchondral bone in knee joints.